PENGARUH PEMBERIAN HADIAH TERHADAP MINAT SISWA DALAM MENULIS TEKS CERPEN PADA SISWA SMP - Diana Aprilianti; Mira Novia Herawati; Heri Isnaini (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Learning with interest in writing texts is basically for all people still lacking, especially among students and students who are not people who are in the field of education. This is because people who are less aware of the benefits of writing. Besides that, there are also quite a lot of obstacles that exist when you want to write, especially in writing a text. Barriers that are usually in the form of laziness and no sense of motivation want to write. The formulation of the problem in this study are: 1) What is a reward in education? 2) What is the effect of giving rewards? This study aims to determine the effect of giving rewards to students' interest in writing texts at SMP. The reward is an award that is proud of all students. Researchers give prizes to encourage students to be more interested in writing. So, with the award given by the teacher, it is expected to be able to make students motivated in learning activities. The approach used during this research is qualitative research. The data collection techniques that will be discussed are questionnaires. The results of this study indicate that students' interest in writing increases. It is seen from the results of the data that show that giving rewards is very influential on student motivation.